Xanthone Biosynthetic Pathway in Plants: A Review - Remali, Juwairiah; Sahidin, Idin; Aizat, Wan Mohd (Frontiers in Plant Science, 2022)
Xanthones are secondary metabolites rich in structural diversity and possess a broad array of pharmacological properties, such as antitumor, antidiabetic, and anti-microbes. These aromatic compounds are found in higher plants, such as Clusiaceae, Hypericaceae, and Gentianaceae, yet their biosynthetic pathways have not been comprehensively updated especially within the last decade (up to 2021). In this review, plant xanthone biosynthesis is detailed to illuminate their intricacies and differences between species. The pathway initially involves the shikimate pathway, either through L-phenylalanine-dependent or -independent pathway, that later forms an intermediate benzophenone, 2,3′,4,6-tetrahydoxybenzophenone. This is followed by a regioselective intramolecular mediated oxidative coupling to form xanthone ring compounds, 1,3,5-trihydroxyxanthone (1,3,5-THX) or 1,3,7-THX, the core precursors for xanthones in most plants. Recent evidence has shed some lights onto the enzymes and reactions involved in this xanthone pathway. In particular, several biosynthetic enzymes have been characterized at both biochemical and molecular levels from various organisms including Hypericum spp., Centaurium erythraea and Garcinia mangostana. Proposed pathways for a plethora of other downstream xanthone derivatives including swertianolin and gambogic acid (derived from 1,3,5-THX) as well as gentisin, hyperixanthone A, α-mangostin, and mangiferin (derived from 1,3,7-THX) have also been thoroughly covered. This review reports one of the most complete xanthone pathways in plants. In the future, the information collected here will be a valuable resource for a more directed molecular works in xanthone-producing plants as well as in synthetic biology application.